Epigenetic Control of Autophagy Related Genes Transcription in Pulpitis via JMJD3 - Yin, Bei; Ma, Qingge; Zhao, Lingyi; Song, Chenghao; Wang, Chenglin; Yu, Fanyuan; Shi, Yu; Ye, Ling (Frontiers in Cell and Developmental Biology, 2021)
Autophagy is an intracellular self-cannibalization process that delivers cytoplasmic components to lysosomes for digestion. Although it was reported to be involved in pulpitis, the regulation of autophagy during pulpitis progression is largely unknown. To figure out the epigenetic regulation of autophagy during pulpitis, we screened several groups of histone methyltransferases and demethylases in response to TNFα treatment and found JMJD3, an H3K27 demethylase, could regulate the expression of several key autophagy genes by mediating the H3K27 methylation directly. Our study highlighted the epigenetic regulation of autophagy genes during pulpitis, which will potentially provide a novel therapeutic strategy.